PENGARUH PEMBERIAN TABLET PENAMBAH DARAH (Fe) TERHADAP KADAR HEMOGLOBIN IBU DI PUSKESMAS KAMANRE - Israini Suriati (Voice of Midwifery, 2016)
Background: Iron deficiency anemia is a disorder that most often occurs during pregnancy. Pregnant women generally experience depletion of iron, so just give a little iron to the fetus is required for normal iron metabolism. Hereafter, they will be anemic at the time of maternal hemoglobin levels fall below 11 g / dl. Objectives: To determine the effect of giving iron tablets for hemoglobin levels of pregnant women in Kamanre Public Health Centers in 2016. Methods: This research is an evaluation study on the provision of iron tablets to pregnant women, where measurements were taken before and after giving of hemoglobin iron tablets. This research used 30 samples that had not received iron tablets during pregnancy. Results: There was no effect of giving iron tablets with status between the initial and finalhemoglobin (p = 0563 > p = 0.05) which proves that there is a distribution change of patients with anemia after giving iron tablets in pregnant women. Suggestion: During pregnancy, pregnant women taking iron tablets according to standard antenatal care during pregnancy is 90 tablets. Key words: Tablet Fe, Hb,Pregnant women